1954
DOI: 10.1039/df9541600201
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of absorption of non-ionic dyes by polyethylene terephthalate

Abstract: Isotherms were measured for the distribution of three pure non-ionic dyes and their binary mixtures between polyethylene terephthalate and water in the presence and absence of benzoic acid. In each case, the equilibrium concentration of dye in the fibre was directly proportional to the concentration in the water. For a binary mixture of greatly dissimilar dyes, each behaved completely independently of the other, while for a mixture of two closely related dyes some interference was noted. The solubilities of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 0 publications
3
43
0
Order By: Relevance
“…The dye which is present in true solution is assumed to be in a monomolecular state, both in the dyebath and in the fiber. 18 ' 93 ' 94 ' 317,319,328 Vickerstaff and Waters 38 obtained Langmuir-type isotherms for the dyeing of four related anthraquinonoid dyes on cellulose acetate. In the previous chapter, Daruwalla has discussed the experimental evidence for state of aggregation of dye in the dyebath and in the substrate.…”
Section: Aqueous Dyeingmentioning
confidence: 99%
“…The dye which is present in true solution is assumed to be in a monomolecular state, both in the dyebath and in the fiber. 18 ' 93 ' 94 ' 317,319,328 Vickerstaff and Waters 38 obtained Langmuir-type isotherms for the dyeing of four related anthraquinonoid dyes on cellulose acetate. In the previous chapter, Daruwalla has discussed the experimental evidence for state of aggregation of dye in the dyebath and in the substrate.…”
Section: Aqueous Dyeingmentioning
confidence: 99%
“…Recent investigators illustrate sorption isotherms obeying only the Langmuir law, sorption isotherms of disperse dyes would obviously depend on the presence of dispersing agents, the dyeing temperature, the dye structure and the fibre type . While a simple linear isotherm is suggested for polyester‐disperse dyeing system in the absence of dispersing agents, more complex models have been found to be suitable for this system in the presence of dyeing auxiliaries .…”
Section: Introductionmentioning
confidence: 99%
“…However, mixture dyeing of the same fiberldye system is still subject to research. The first attempts to describe the mutual interactions of dyes on dyeing hydrophobic substrates with binary mixtures of disperse dyes were made by Vickerstaff and Waters1 and Bird and Rhyner.2 Further contributions were made, in particular, by Schuler and Remington, 3 Johnson et al,4 and Hoffmann et al 5 These equilibrium sorption stydies revealed that the saturation values in hydrophobic substrates of binary dye mixtures of certain disperse dyes are additive, but the dyes of binary mixtures of similar chemical constitution are sorbed to a smaller extent than when they are applied individually.…”
Section: Introductionmentioning
confidence: 99%